The beneficial effect of csDMARDs co-medication on drug persistence of first-line TNF inhibitor in rheumatoid arthritis patients: data from Czech ATTRA registry - Skácelová, Martina; Nekvindová, Lucie; Mann, Heřman; Závada, Jakub; Křístková, Zlatuše; Vencovský, Jiří; Pavelka, Karel; Horák, Pavel (Rheumatology international, 2022)
The study aimed to compare treatment retention for first-line TNF inhibitor (TNFi) in the ATTRA registry patients receiving either combination with conventional synthetic DMARDs or TNFi as monotherapy. A retrospective multicenter study analyzed data of all adult patients with rheumatoid arthritis (n = 3032) starting TNF inhibitor as the first-line biological therapy in combination with csDMARDs or in monotherapy from January 1st 2012 to December 31st 2020. Kaplan-Meier method was employed to calculate drug retentions. Survival curves of treatment retentions were compared through Log-rank test between the studied subgroups. The hazard ratio for drug discontinuation was assessed through univariate cox regression models. In patients who started the first line TNFi therapy, the median treatment retention was 47.7 (42.2; 53.1) months for combination therapy and 22.7 (14.9; 30.6) months for TNFi monotherapy (p < 0.001). Estimated one-year survival was higher in patients on TNFi combined with csDMARDs as compared with TNFi monotherapy (75.3% vs 65.7%); two-year survival rate was 63.2% vs 49.2%, three-year survival rate was 55.4% vs 42.4% and five-year survival 44.9% vs 26.4% of patients. The estimated survival on the first TNFi was higher in patients taking combination therapy with methotrexate than with other csDMARDs (p = 0.003). Use of csDMARDs co-medication was associated with significantly better first TNFi drug survival compared to monotherapy. The combination of TNFi with MTX is more effective than the combination with leflunomide, which did not demonstrate a significant effect.
Keywords: retrospektivní studie; Tumor Necrosis Factor Inhibitors; Humans; lidé; Tumor Necrosis Factor-alpha; Arthritis, Rheumatoid; Retrospective Studies; registrace; Czech Republic; Treatment Outcome; methotrexát; Antirheumatic Agents; Adult; TNF-alfa; revmatoidní artritida; výsledek terapie; antirevmatika; inhibitory TNF; dospělí; Drug Therapy, Combination; Registries; Česká republika; Methotrexate; kombinovaná farmakoterapie